‘Mere Jelly’: The Bodies of Networked Learners - Bayne, Siân (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines the issue of embodiment and its implications for networked learners. Drawing on an exploration of relevant aspects of cultural theory and on interviews with students and teachers, it discusses the effects of technological mediation on the way in which we experience our embodiment in online learning contexts. It does this in two main strands. The first is a consideration of the mind-body split and the way in which this dualism is being challenged in contemporary theory and in the online classroom. The second is a discussion of the ways in which the body is ‘re-articulated’ by its relation to the machinic, and the effect such re-articulation appears to have on the experience of learners.